An explorative factor analysis of competency mapping for IT professionals - Jaskiran Kaur; Geetika Madaan; Sayeeduzzafar Qazi; Pretty Bhalla (Administrative Sciences, 2023)
Purpose: The current research aimed to evaluate IT personnel proficiency levels at various management levels. This study aimed to learn how competency mapping is used to analyse the blend of skills among various people to create the most cohesive team and deliver higher-quality work. Design/methodology/approach: A total of 548 IT workers participated in the research, which looked at how competence mapping influences various HR processes, including talent acquisition, induction, training and development, assessment, etc. This research used reliability analysis, descriptive analysis, correlation analysis, linear regression, and the t-test to reach its results. Findings: This research made use of reliability statistics, regression analysis, correlation analysis, ANOVA analysis, the t-test, and descriptive statistics to reach its results. The research discovered that medium-level managers' talents were greater than anticipated when comparing lower and higher levels of management. Additionally, there were significant differences among employees at different levels of management. Communication and training may help reduce competence gaps. Practical implications: In comparing other levels of management, this article may help HR practitioners identify which abilities are more relevant to a certain management level. It can provide more insight into using a competence mapping approach to improve performance. Originality/value: The outputs of the competency mapping approach are essential because they can help individuals and businesses gain a better comprehension of the knowledge, abilities, and skills required to accomplish a job.
Keywords: 350; competency; competency mapping; IT sector; leadership skills; personal qualities; teamwork